Does the minimum wage reduce wage inequality? Evidence from Thailand - Attakrit Leckcivilize (IZA Journal of Labor & Development, 2015)
Most of the minimum wage literature in developing countries provides supporting evidence of its effectiveness in reducing wage inequality. Using minimum wage data from Thailand (1985-2010), I find rather mixed outcomes. The minimum wage seems to help compress the lower part of wage distribution for employees in large businesses. However, the effect does not extend to small and medium firms in the covered sector. In contrast with its role as a benchmark for wage adjustment in Latin America, the minimum wage in Thailand does not reduce overall wage inequality owing to the high non-compliance rate and weak law enforcement, particularly in the informal sector.
Keywords: J38; O17; 330; Minimum wage; Thailand; Wage inequality; Formal and informal sector; Compliance